An Unusual Cervical Mass in the Hyoid Bone: Intermediate-Grade Chondrosarcoma - Caglar, Ozge (Case Rep Otolaryngol, 2019)
We describe a case of a 31-year-old woman with a chondrosarcoma of the hyoid bone. The patient presented with a mass in the left submandibular region. Fine-needle aspiration cytology suggested chondroma, but further imaging investigation with CT revealed an exophytic tumor originating from the body of the hyoid bone. Histopathology of the surgical specimen confirmed the diagnosis of a intermediate-grade chondrosarcoma. Chondrosarcomas account for 11% of all bone cancers. Primary sites of the head and the neck include the nasal cavity, the skull base, the maxilla, the mandible. Chondrosarcomas of the hyoid bone are very rare, with only 23 cases previously reported in the literature.